Integrated packaging systems for transportation and distribution - Ebeling, Charles W (Packaging and converting technology, 1990)
Identifies the cost sensitive areas for each activity in the logistical system. Illustrates how packaging in addition to protecting and preserving contents can affect total system cost efficiency if designed to adapt well to unitized shipping methods and equipment: efficiently utilize warehouse stor.